Fabrication and formation mechanism of Ce2O3–CeO2–CuO–MnO2/CNTs catalysts and application in low-temperature NO reduction with NH3. Issue 70 (11th July 2016) - Zhang, Yanbing; Zheng, Yuying; Chen, Xuehong; Fu, Binbin
Abstract : Ce2 O3 –CeO2 –CuO–MnO2 /CNTs catalysts were synthesized via a redox strategy, and presented 58–85% NO conversion at 80–180 °C. Abstract : Ce2 O3 –CeO2 –CuO–MnO2 /CNTs catalysts were synthesized via a redox strategy, and presented 58–85% NO conversion at 80–180 °C. The 6% Ce2 O3 –CeO2 –CuO–MnO2 /CNTs catalyst displayed the optimal activity, which may be owing to the generation of amorphous mixed metal-oxide catalysts, and higher contents of Ce 3+ and surface oxygen (Oy ). The formation mechanism of the catalysts was proposed.